Pengaruh Konsentrasi Nutrisi dan Beberapa Media Tanam terhadap Pertumbuhan dan Hasil Tanaman Seledri (Apium graveolens L.) dengan Sistem Wick secara Hidroponik - Lestari, Dina; Armaini; Gusmawartati (Jurnal Hortikultura Indonesia, 2020)
Cultivation with the hydroponic wick system using nutrients with various concentrations in the use of several planting media is expected to be able to optimize the growth and production of celery. This study aims to determine the effect of planting media on providing nutrient concentration and to obtain the best planting media and the right nutrient concentration with the hydroponic wick system. The research was conducted at the screen house, Faculty of Agriculture, Riau University, from June to October 2019. The research used a Split Plot Design, consisting of the main nutrient plots: AB-MIX 1000 ppm, AB-MIX 1200 ppm, AB-MIX 1400 ppm, AB- MIX 1600 ppm, subplots of planting media: husk charcoal, cocopeat, sawdust, carried out 3 replications. The variables observed were plant height, number of main petioles, number of leaves, fresh weight of consumption per plant, and weight of roots. The results showed that there was a good effect of using sawdust growing media with nutrients of 1000-1200 ppm on the growth and yield of celery. Giving nutrition 1000-1200 ppm shows good results and the treatment of sawdust growing media can increase the growth and yield of celery.Keywords: celery, growing media, hydroponic wick system, nutrient concentration